Britain in the world economy since 1880 - Alford, Bernard W. E. 1937- (A social and economic history of England, 1996)
Bernard Alford reviews the changing role, and diminishing influence, of Britain within the international economy across the century that saw both the apogee and loss of Britain's empire, and her transformation from globe-straddling superpower to offshore and indecisive member of the European Community. The study of this changing relationship offers a uniquely revealing angle from which to analyse Britain's broader economic development. Professor Alford takes full advantage of that: and his conclusions do not make for comfortable reading.